Emotional Change-Associated T Cell Mobilization at the Early Stage of a Mouse Model of Multiple Sclerosis - Piras, Giuseppa; Rattazzi, Lorenza; McDermott, Adam; Deacon, Robert; D'acquisto, Fulvio (Frontiers in Immunology, 2013)
Autoimmune diseases like multiple sclerosis are known to be associated with debilitating emotional disorders that manifest long before the flaring of motor dysfunctions. Given the emerging role of T cells in controlling both emotions and autoimmunity, in this study we explored possible correlation between T cell activation and changes in emotional behavior in a mouse model of multiple sclerosis. Our results showed a significant increase in blood circulating T cells as soon as at day 4 post-immunization. This lymphocytosis remained stable with time and preceded the infiltration of T cell in the CNS. The kinetic of T cell entry in the blood matched the kinetic of changes in behavior measured using the open field test. Treatment with glatiramer acetate, a well-known immunomodulatory drug for multiple sclerosis, suppressed behavioral changes while retaining the T cells in the draining lymph nodes. Together these results provide evidence of a positive correlation between the emigration of T cells in circulation and changes in emotions during chronic inflammatory diseases. The validation of these findings in the clinic might help to better understand the cause of the emotional and psychological burden of patients suffering multiple sclerosis or other autoimmune diseases. Most importantly our study suggests novel therapeutic venues for the treatment of the emotional changes associated with autoimmunity.